Phylotaxonomic analysis uncovers underestimated species diversity within the genus Rossellomorea with description of selenium-resistant Rossellomorea yichunensis sp. nov - Jiejie Kong; Ziyue Fu; Qianyang Zhang; Yiqin Liu; Zixuan Luo; Zhigang Zhao; Liangliang Liu; Xiaolong Liu; Dan Xu; Xingjie Li; Daofeng Zhang (BMC Microbiology)
Abstract A novel Gram-stain-positive, aerobic, motile, rod-shaped strain, designated as YC4-1 T, was isolated from rhizosphere soil of Ageratum conyzoides collected from a selenium-rich area in Yichun, Jiangxi Province, China. Strain YC4-1 T grew optimally at pH 7.0–8.0, 28.0–37.0℃, and 0.5–3.0% (w/v) NaCl; could tolerate up to 5,000 mg/L Na2SeO3; and exhibited the ability to biosynthesize selenium nanoparticles. The chemotaxonomic characterization revealed that the polar lipids of strain YC4-1 T were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, and an unidentified lipid. The major cellular fatty acids were anteiso-C15:0 and iso-C15:0, and the respiratory quinone was MK-7. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain YC4-1 T shared the highest similarity of 99.0% to Rossellomorea arthrocnemi EAR8T and clusters within the genus Rossellomorea. The genome size was 4,694,377 bp in length, with a DNA G + C content of 41.5%. Phylogenomic reconstruction using the bac120 gene set implied that strain YC4-1 T formed a distinct clade clustering eight unclassified bacteria. The average nucleotide identity (ANI) and the digital DNA–DNA hybridization (dDDH) values between strain YC4-1 T and type strains of the genus Rossellomorea were all below the respective thresholds of ANI and dDDH for species delimitation. Based on phylogenetic analyses and phenotypic and chemotaxonomic characteristics, strain YC4-1 T is concluded to represent a novel species of the genus Rossellomorea, for which the name Rossellomorea yichunensis sp. nov. (YC4-1 T = GDMCC 1.3541 T = KCTC 43479 T) is proposed. In addition, we also identified 14 uncharacterized bacterial genospecies clustered within the genus Rossellomorea and sharing 16S rRNA gene similarities of > 98.7% with strain YC4-1 T, which suggested that the species diversity of this genus is underestimated when using 16S rRNA gene sequences for initial identification. This study also investigated the genetic potential on selenocompound metabolism of bacteria within the genus Rossellomorea and highlighted the potential application in selenium bioremediation and nano-biotechnology.